Battle of Surigao Strait - Tully, Anthony P. 1961-; EBSCOhost eBook Collection (Bloomington Indiana University Press, 2009)
Surigao Strait in the Philippine Islands was the scene of a major battleship duel during the Battle of Leyte Gulf. Because the battle was fought at night and had few survivors on the Japanese side, the events of that naval engagement have been passed down in garbled accounts. Anthony P. Tully pulls together all of the existing documentary material, including newly discovered accounts and a careful analysis of U.S. Navy action reports, to create a new and more detailed description of the action. In several.
Prologue "Retiring towards the enemy." -- 1. "I have returned." -- 2. "Bah. We will do our best." -- 3. "We are going to participate in a surface special attack -- 4. "It is deemed advisable for 2YB to storm into Leyte Gulf." -- 5. "He gallantly came to a stop and started rescue work" -- 6. "Everybody aboard thought a BB could force a narrow strait" -- 7. "Make all ready for night battle" -- 8. "A most tragic dispatch" -- 9. "Take out the searchlight!" -- 10. "He wished them to know he was penetrating alone."
Electronic reproduction.
Keywords: Leyte Gulf, Battle of, Philippines, 1944.; Electronic books; Surigao Strait (Philippines) -- History, Military -- 20th century